Targeting the epigenome with advanced delivery strategies for epigenetic modulators - Sonia Guha; Yogeswaran Jagadeesan; Murali Monohar Pandey; Anupama Mittal; Deepak Chitkara (Bioengineering & Translational Medicine)
Abstract Epigenetics mechanisms play a significant role in human diseases by altering DNA methylation status, chromatin structure, and/or modifying histone proteins. By modulating the epigenetic status, the expression of genes can be regulated without any change in the DNA sequence itself. Epigenetic drugs exhibit promising therapeutic efficacy against several epigenetically originated diseases including several cancers, neurodegenerative diseases, metabolic disorders, cardiovascular disorders, and so forth. Currently, a considerable amount of research is focused on discovering new drug molecules to combat the existing research gap in epigenetic drug therapy. A novel and efficient delivery system can be established as a promising approach to overcome the drawbacks associated with the current epigenetic modulators. Therefore, formulating the existing epigenetic drugs with distinct encapsulation strategies in nanocarriers, including solid lipid nanoparticles, nanogels, bio‐engineered nanocarriers, liposomes, surface modified nanoparticles, and polymer–drug conjugates have been examined for therapeutic efficacy. Nonetheless, several epigenetic modulators are untouched for their therapeutic potential through different delivery strategies. This review provides a comprehensive up to date discussion on the research findings of various epigenetics mechanism, epigenetic modulators, and delivery strategies utilized to improve their therapeutic outcome. Furthermore, this review also highlights the recently emerged CRISPR tool for epigenome editing.